KONTRIBUSI ETOS KERJA ISLAMI DAN PELATIHAN TERHADAP KINERJA GURU MADRASAH TSANAWIYAH SWASTA (MTSS) SE-KOTA PADANG PANJANG - Asrizallis Asrizallis (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
In this quantitative study the researcher tested three hypotheses 1) the work ethos of Islamic contributed significantly toward the teachers’ job performance; 2) the training contributed significantly toward the teachers’ job performance; 3) simultaneously, the work ethos of Islamic and training contributed significantly toward the teachers’ job performance in Islamic Junior High School Padang Panjang. Research samples were 58 teachers which were selected from 152 population. Research data were collected through questionnaire. The results revealed that a) the work ethos of Islamic contributed significantly (26,50%) toward the teachers’ job performance; b) the teachers’ training contributed significantly (26,00%) toward the teachers’ job performance; c) simultaneously, the work ethos of Islamic and training contributed significantly (40,70%) toward the teachers’ job performance. Keywords: Teachers’ Job Performance, Work Ethos of Islamic, Training, Islamic Junior High School